Bromodimethyl Sulphonium Bromide Catalyzed Efficient One Pot Synthesis of 3,4-Dihydropyrimidine-2-(1H)-ones: An Improved High Yielding Simple Protocol for The Biginelli Reaction - D. Bhinge, Somanath; Saifuddin Khalid, Md.; Sunil Kumar, B. (Asian Journal of Chemistry, 2010)
A novel one pot cyclocondensation of aldehyde, β-ketoester and urea or thiourea in acetonitrile by using bromodimethyl sulphonium bromide (BSB) under mild conditions affording 3,4- dihydropyrimidine-2-(1H) ones in excellent yield is described.